Fintech and blockchain: a bibliometric analysis / Aiza Noorsuraya Muhammad Abkari - Muhammad Abkari, Aiza Noorsuraya (2022)
This bibliometric analysis aims to provide quantitative information on FinTech and Blockchain. Specifically, this study focuses on publishing trends, research areas, major contributing journals, countries and organizations, most productive authors, and articles with the highest citations. A total of 5,808 documents related to FinTech and Blockchain were gathered from the Web of Science Core Collection (WOSCC) database, covering the period 2015 - 2021. The study notices that finance research has developed significant bibliometric velocity. The citations and publications on the other hand are expected to increase in the future. USA, China, and England published the most documents. Moreover, these countries were still outperforming all other countries with the highest citations. MIT, The Hong Kong Polytechnic University, RMIT University Melbourne, and UCL had the most articles published while Harvard University, National Bureau of Economic Research, Montpellier Business School, and Hong Kong Polytech University led the institutions globally based on citations. Asongu; S.A., Shahbaz; M. and Choi T.M. appeared to be the most prolific authors while the highly cited researchers were Shahbaz; M. , Choi; T.M. and Nasir; M.A. Technological Forecasting and Social Change, Energy Policy and Journal of Business Research were the top three most active journals that published articles related to Fintech field. Using co-occurrence analysis, (i) technological development, (ii) artificial intelligence (Al) and digital transformation, (iii) blockchain technology and sustainable supply chains, and (iv) blockchain and digital currency were the existing main research hotspots in the FinTech field. However, the issue coming from a lack of awareness about new technology development will escalate the difficulties and have an impact on FinTech's product quality performance. Besides, those who dismiss FinTech may not recognize that they are contributing to the technology's future ineffectiveness. Lastly, Blockchain technology, digital currency, and Covid-19 can be considered as future research directions.